I often read that the counterfactual conditional "is standardly held to be closed under entailment", but I am not sure if I understand what it means: Say p counterfactually implies q, and q implies r; does p counterfactually imply r? And would this be the correct way to write it down?
((p ☐→ q) ∧ (q → r)) → (p ☐→ r)
I'm inclined to say yes, but I'd like to have a solid proof. I tried to look my question up in different handbooks and Lewis's "Counterfactuals", but was unable to answer the question (which is probably my fault).
I'd be happy for any input and recommendations for further reading!